2000
DOI: 10.1634/theoncologist.5-2004-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy-Associated Anemia: The Scope of the Problem

Abstract: The impact of anemia on cancer patients undergoing chemotherapy is well established, but only recently has the prevalence of anemia in patients receiving radiotherapy received much attention. Many cancer patients present with anemia prior to radiotherapy, and even more experience anemia or a worsening of anemia at some point during treatment. However, the problem of anemia is often ignored because patients may experience only functional anemia, defined as a hemoglobin level less than 12 g/dl. Unless physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 7 publications
1
19
0
6
Order By: Relevance
“…This shows that the prevalence of anemia among our subjects increased by 2% after the chemotherapy. Our pre-and post-chemotherapy prevalence of anemia was almost equivalent to the preand post-radiotherapy prevalence of anemia, which was reported by Harrison et al in a retrospective study on breast cancer patients (41% and 44%, respectively) (14). Our postchemotherapy prevalence is concordant with the findings of Kirshner et al who reported the rate of anemia to be 40% among their patients after the chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…This shows that the prevalence of anemia among our subjects increased by 2% after the chemotherapy. Our pre-and post-chemotherapy prevalence of anemia was almost equivalent to the preand post-radiotherapy prevalence of anemia, which was reported by Harrison et al in a retrospective study on breast cancer patients (41% and 44%, respectively) (14). Our postchemotherapy prevalence is concordant with the findings of Kirshner et al who reported the rate of anemia to be 40% among their patients after the chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…As studies show that many, but not all, cancer patients experience anaemia (Coiffier, 1998;Dalton et al, 1998;Groopman and Itri, 1999;Harrison et al, 2000), it would be of great benefit to be able to predict whether a patient is at high risk of developing anaemia and/or has a low tolerance to the complications of anaemia and blood transfusions. Such knowledge would assist physicians in monitoring patients more closely and/or administering therapy with an erythropoietic agent before anaemia becomes symptomatic.…”
Section: Key Uncertainties Surrounding the Management Of Anaemic Cancmentioning
confidence: 99%
“…In a study by Harrison et al (2000), 48% of patients presenting for radiotherapy for solid tumours were anaemic (haemoglobin < 12 g dl -1 ) before treatment; this figure increased to 57% with the completion of therapy.…”
mentioning
confidence: 98%
“…This has been described as functional anemia (Hb levels ,12 g/dL) as opposed to physiologic anemia (Hb levels #8 g/dL). 67 According to the guidelines, ESA treatment should not be initiated in such a patient, yet some form of intervention is clearly required because the patient has symptoms (eg, fatigue) that need to be addressed. In such a case, the first step should always be to consider other potential causes of anemia symptoms.…”
mentioning
confidence: 99%